High-temperature-resistant release paper and preparation method thereof

By introducing silicon quantum dots on the paper base surface and applying fluorocarbon coating, the problem of failure of traditional release paper in high temperature environments is solved, and higher high temperature resistance and anti-adhesion performance are achieved.

CN119593254APending Publication Date: 2025-03-11ZHEJIANG MINGHUI NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411943036.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Traditional release papers are prone to failure in high temperature environments, resulting in surface coating peeling and paper-based aging.

Method used

The paper-based raw material is soaked in a silicon quantum dot solution, the silicon quantum dot is introduced, and the fluorocarbon coating is coated on the surface to improve the high temperature resistance and anti-adhesion properties of the paper-based base.

Benefits of technology

It significantly improves the high temperature resistance of the paper base, enhances the adhesion to the coating, avoids the coating falling off, and improves the mechanical strength and wear resistance of the paper base.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention relates to the technical field of release paper, and provides high-temperature-resistant release paper and a preparation method thereof. The preparation method comprises the following steps: S100, soaking a paper-based raw material in a silicon quantum dot solution, taking out the treated paper-based raw material, and performing freeze-drying treatment to obtain a modified paper base; and S200, coating the surface of the modified paper base with a fluorocarbon coating to obtain the high-temperature-resistant release paper. The silicon quantum dot solution is adopted for soaking treatment, so that the surface characteristics of the paper base are improved, the high temperature resistance is improved, and the adhesive force with a coating is enhanced; meanwhile, through coating of the fluorocarbon coating, the high-temperature resistance, adhesion resistance, water resistance and corrosion resistance of the paper base are enhanced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of release paper, and in particular to a high temperature resistant release paper and a preparation method thereof. Background Art

[0002] Release paper is widely used in many fields, especially in industrial production and packaging processes. As an important auxiliary material, it is mainly used to isolate and protect the surface of other materials to prevent adhesion. Traditional release paper generally adopts surface coating treatment technology to achieve anti-sticking effect by applying different types of coatings.

[0003] However, the performance of existing release papers in high temperature environments is often limited, especially in applications that require long-term high temperature resistance and good release performance. Traditional release papers are easily ineffective due to high temperatures, leading to problems such as surface coating shedding and paper base aging. Summary of the invention

[0004] Therefore, the present invention provides a high temperature resistant release paper and a preparation method thereof, aiming to solve the problem that traditional release paper is easily ineffective due to high temperature, resulting in shedding of the surface coating and aging of the paper base. Silicon quantum dots are introduced on the surface of the paper base by immersion treatment with a silicon quantum dot solution, thereby improving the surface properties of the paper base, improving the high temperature resistance, and enhancing the adhesion to the coating; at the same time, by coating with fluorocarbon coating, the high temperature resistance, anti-adhesion, waterproof and anti-corrosion capabilities of the paper base are enhanced.

[0005] In order to solve the above problems, the first object of the present invention is to provide a method for preparing high temperature resistant release paper;

[0006] The second object of the present invention is to provide a high temperature resistant release paper;

[0007] To achieve the first purpose of the present invention, the present invention provides a high temperature resistant release paper and a preparation method thereof, the preparation method comprising: S100, soaking a paper base raw material in a silicon quantum dot solution, taking out the treated paper base raw material and performing freeze drying treatment to obtain a modified paper base; S200, coating a fluorocarbon coating on the surface of the modified paper base to obtain a high temperature resistant release paper; wherein, the preparation method of the silicon quantum dot solution adopts the following steps: S110, dissolving a reducing agent in deionized water, and adding a silicon source to obtain a first mixed solution; S120, transferring the mixed solution into a reactor, heating the reaction at a temperature of 140 to 220°C for 2 to 24 hours, and cooling to obtain a second mixed solution; S130, adding a surface modifier to the second mixed solution, and performing stirring treatment, centrifugal treatment, and washing treatment in sequence to obtain a silicon quantum dot solvent.

[0008] In a technical solution of the present invention, in step S110, the silicon source includes at least one of silicon tetrachloride and trichlorosilane; and / or the reducing agent includes at least one of lithium aluminum hydride, hydrogen, and sodium borohydride; and / or the mass ratio of the silicon source to the reducing agent is 1:(0.5-2).

[0009] In a technical solution of the present invention, in step S130, the surface modifier includes at least one of organosilane, polyethylene glycol, hexadecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate, and polyacrylamide; and / or the mass ratio of the surface modifier to the second mixed solution is 1:(10-200).

[0010] In one technical solution of the present invention, in step S100, the solubility of the silicon quantum dot solution is between 1 and 10 mg / mL; and / or the temperature of the freeze-drying treatment is between -40 and -60°C; and / or the time of the freeze-drying treatment is between 12 and 24 hours.

[0011] In a technical solution of the present invention, between step S100 and step S200, the following further comprises: S210, plasma treatment of the modified paper base.

[0012] In a technical solution of the present invention, in step S200, the preparation method of the fluorocarbon coating adopts the following steps: S201, adding polytetrafluoroethylene to a fluorinated solvent, heating and stirring, and adding nano zinc oxide and nylon powder in sequence to obtain a mixed solution; S202, adding chlorosilane to the mixed solution to obtain a fluorocarbon coating.

[0013] In one technical solution of the present invention, in the fluorocarbon coating, the mass ratio of polytetrafluoroethylene, nano zinc oxide, nylon powder and chlorosilane is (30-4): (16-2): (12-1.6): 1; and / or the viscosity of the fluorocarbon coating is between 150 and 300 cP.

[0014] In one technical solution of the present invention, in step S201, the temperature of the heating and stirring treatment is between 50 and 80°C.

[0015] In a technical solution of the present invention, the thickness of the silicon quantum dot layer is between 1 and 5 μm; the thickness of the fluorocarbon coating is between 5 and 15 μm; and the thickness of the paper-based raw material is between 50 and 150 μm.

[0016] To achieve the second purpose of the present invention, the present invention provides a high temperature resistant release paper prepared by using any one of the above technical solutions.

[0017] After adopting the technical solution of the present invention, the following technical effects can be achieved:

[0018] (1) Through the introduction of silicon quantum dots and the coating of fluorocarbon coatings, the high temperature resistance of the paper base has been significantly enhanced. The high thermal stability of silicon quantum dots and the high temperature resistance of fluorocarbon coatings enable the release paper to be used for a long time in a high temperature environment without being easily degraded, invalidated or having the coating fall off;

[0019] (2) Fluorocarbon coating has an anti-adhesion effect, which can effectively isolate and protect the paper base surface, prevent adhesion with other materials, and enhance the corrosion resistance and anti-pollution ability of the paper base, keeping the paper base surface clean and stable;

[0020] (3) The silicon-oxygen bonds between silicon quantum dots and the paper base improve the strength and toughness of the paper base, making the release paper more durable. The addition of fluorocarbon coating improves the adhesion between the coating and the paper base, preventing the coating from falling off, further improving the mechanical strength and wear resistance of the paper base, and adapting to higher intensity usage environments. DETAILED DESCRIPTION

[0021] Reference will be made below to various exemplary embodiments, features, and aspects of the disclosure.

[0022] The word “exemplary” is used exclusively herein to mean “serving as an example, example, or illustration.” Any embodiment described herein as “exemplary” is not necessarily to be construed as preferred or advantageous over other embodiments.

[0023] The term "and / or" herein is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the term "at least one" herein represents any combination of at least two of any one or more of a plurality of. For example, including at least one of A, B, and C can represent including any one or more elements selected from the set consisting of A, B, and C.

[0024] It should be understood that the terms "first", "second", "third", etc. in the claims and specifications of the present disclosure are used to distinguish different objects rather than to describe a specific order. The terms "include" and "comprise" used in the specifications and claims of the present disclosure indicate the presence of the described features, wholes, steps, operations, elements and / or components, but do not exclude the presence or addition of one or more other features, wholes, steps, operations, elements, components and / or their collections.

[0025] In addition, in order to better illustrate the present disclosure, numerous specific details are given in the following specific embodiments. It should be understood by those skilled in the art that the present disclosure can also be implemented without certain specific details. In some examples, methods, means, components and circuits well known to those skilled in the art are not described in detail in order to highlight the subject matter of the present disclosure.

[0026] Release paper is widely used in many fields, especially in industrial production and packaging processes. As an important auxiliary material, it is mainly used to isolate and protect the surface of other materials to prevent adhesion. Traditional release paper generally adopts surface coating treatment technology to achieve anti-sticking effect by applying different types of coatings.

[0027] However, the performance of existing release papers in high temperature environments is often limited, especially in applications that require long-term high temperature resistance and good release performance. Traditional release papers are easily ineffective due to high temperatures, leading to problems such as surface coating shedding and paper base aging.

[0028] Therefore, the present invention provides a high temperature resistant release paper and a preparation method thereof, which solves the problem that traditional release paper is easily ineffective due to high temperature, resulting in shedding of the surface coating and aging of the paper base. Silicon quantum dots are introduced on the surface of the paper base by immersion treatment with a silicon quantum dot solution, thereby improving the surface properties of the paper base, improving the high temperature resistance, and enhancing the adhesion to the coating; at the same time, by coating with fluorocarbon coating, the high temperature resistance, anti-adhesion, waterproof and anti-corrosion capabilities of the paper base are enhanced.

[0029] A method for preparing a high temperature resistant release paper comprises the following steps:

[0030] S100, soaking the paper-based raw material in a silicon quantum dot solution, taking out the treated paper-based raw material and performing freeze-drying treatment to obtain a modified paper-based raw material;

[0031] S200, coating the fluorocarbon coating on the surface of the modified paper base to obtain a high temperature resistant release paper.

[0032] Preferably, the cellulose of the paper-based raw material contains abundant hydroxyl (-OH) functional groups, which can chemically react with silicon ions in the silicon source to form stable silicon-oxygen bonds, thereby enhancing the functionality and thermal stability of the paper base, improving its tensile strength and toughness, and making the release paper of the present application more durable; in addition, the silicon quantum dot solution has good thermal stability, which can effectively improve the high temperature resistance of the paper base, making the paper base less prone to degradation or failure in a high temperature environment, and meeting the high temperature demolding requirements; the introduction of silicon quantum dots improves the surface hydrophilicity and hydrophobicity of the paper base, enhances the oil resistance and water resistance of the paper base, and improves the release performance. When used in conjunction with fluorocarbon coatings, it can further improve the anti-pollution and anti-corrosion capabilities of the paper base.

[0033] Furthermore, the preparation method of the silicon quantum dot solution adopts the following steps:

[0034] S110, dissolving a reducing agent in deionized water, and adding a silicon source to obtain a first mixed solution;

[0035] S120, transferring the mixed solution into a reaction kettle, heating the reaction at a temperature of 140 to 220° C. for 2 to 24 hours, and cooling the mixture to obtain a second mixed solution;

[0036] S130, adding a surface modifier to the second mixed solution, and performing stirring treatment, centrifugal treatment, and washing treatment in sequence to obtain a silicon quantum dot solvent.

[0037] Preferably, a reducing agent is mixed with a silicon source to ensure that the silicon source undergoes a reduction reaction, thereby generating silicon ions or silicon nanoparticles. The selection and amount of the reducing agent will directly affect the morphology, size and surface state of the silicon quantum dots. The mixed solution is transferred into a reactor, and the reduction reaction of the silicon source is promoted under heating conditions to generate silicon quantum dots. Under high temperature conditions, the silicon ions aggregate and gradually nucleate to form larger silicon nanoparticles, and silicon quantum dots are generated through further aggregation. After the silicon quantum dots are formed, a surface modifier is added to adjust the surface properties of the quantum dots. Surface modification can improve the dispersibility and stability of the silicon quantum dots, ensuring that they remain dispersed in an aqueous phase or other solvents for a long time. At the same time, it can enhance the compatibility of the silicon quantum dots with other materials, and can better combine with fluorocarbon coatings and paper-based raw materials.

[0038] Preferably, the silicon source includes at least one of silicon tetrachloride and trichlorosilane. The silicon quantum dots generated by silicon tetrachloride are relatively stable. Trichlorosilane easily forms silicon-oxygen bonds during hydrolysis and can react with surface modifiers to enhance the stability of silicon quantum dots. The reducing agent includes at least one of lithium aluminum hydride, hydrogen, and sodium borohydride. Lithium aluminum hydride can reduce the chloride ions in the silicon source to generate purer silicon quantum dots, which helps to improve the purity and stability of silicon quantum dots and enhance the performance at high temperatures. Hydrogen helps the oxides in the silicon source to be converted into silicon through a reduction reaction. The generated silicon quantum dots are usually more uniform, the surface is more active, and suitable for surface modification. Sodium borohydride reduces the silicon source to silicon quantum dots, which can effectively control the size and morphology of the quantum dots. By controlling the mass ratio of the silicon source to the reducing agent between 1: (10-200), the reaction between the silicon source and the reducing agent will be effective and stable, avoiding the problem of excessive reduction or insufficient reaction. A reasonable mass ratio helps to generate more uniform silicon quantum dots and improve their stability and performance.

[0039] Preferably, the solubility of the silicon quantum dot solution is between 1 and 10 mg / mL, and the silicon quantum dots can be evenly dispersed in the solution, ensuring that the paper-based raw material can fully adsorb the silicon quantum dots. Too high a concentration may cause the quantum dots to aggregate in the solution to form agglomerates, while too low a concentration may result in insufficient adsorption and fail to achieve the expected modification effect.

[0040] Preferably, the temperature of the freeze drying treatment is between -40 and -60°C, which can effectively remove excess water or solvent from the surface of the paper base, avoid material degradation that may be caused by drying at room temperature, and help keep the structure of the paper base material from thermal damage, so that the silicon quantum dots are evenly distributed on the paper base. In addition, the lower temperature helps to reduce bubbles or solvent residues during the entire drying process, making the paper base surface smoother and flatter, and enhancing the adhesion and stability of the coating. The freeze drying treatment time is between 12 and 24 hours, which helps to completely remove the solvent or water in the paper base material while keeping the morphology of the paper base intact. If the freeze drying time is too short, the solvent or water may not be completely removed, resulting in the possibility of residual solvent or excessive water in the final product, affecting its subsequent performance. Too long a time may lead to some unnecessary energy consumption or excessive processing.

[0041] Furthermore, between step S100 and step S200, the method further includes: S210, plasma treatment of the modified paper base.

[0042] Preferably, the plasma treatment step is: placing the modified paper base into a plasma treatment device, selecting oxygen for plasma treatment for 1-5 minutes, and adjusting the gas flow and power according to the equipment requirements; through plasma treatment, oxygen-containing functional groups such as hydroxyl groups, carboxyl groups, etc. can be generated on the surface of the paper base, thereby increasing the hydrophilicity of the paper base surface, making it easier to combine with the fluorocarbon coating, avoiding the coating from peeling off or falling off during subsequent use, and improving the stability and high temperature resistance of the coating; at the same time, plasma treatment not only changes the chemical properties of the paper base, but also changes its surface microstructure, increases the micro-roughness of the paper base surface, can promote more uniform coating of the fluorocarbon coating, prevent the coating from being uneven or falling off, and improve the functionality of the paper base. In addition, plasma treatment enhances the antioxidant properties of the paper base by introducing oxidizing groups on the surface of the paper base, thereby maintaining better stability in a high temperature environment.

[0043] Further, in step S200, the preparation method of the fluorocarbon coating adopts the following steps:

[0044] S201, adding polytetrafluoroethylene to a fluorinated solvent, and adding nano zinc oxide and nylon powder in sequence while heating and stirring to obtain a mixed solution;

[0045] S202, adding chlorosilane to the mixed solution to obtain a fluorocarbon coating.

[0046] Preferably, in the fluorocarbon coating, the mass ratio of polytetrafluoroethylene, nano zinc oxide, nylon powder, and chlorosilane is (30-4): (16-2): (12-1.6): 1. Polytetrafluoroethylene has excellent chemical resistance, high temperature resistance and low friction, and is often used in anti-stick, corrosion-resistant and high temperature resistant coatings; nano zinc oxide provides antibacterial, anti-ultraviolet and anti-oxidation functions, and can enhance the stability and adhesion of the coating, while improving the anti-pollution performance; nylon powder increases the wear resistance and structural strength of the coating, improves the mechanical strength, toughness and impact resistance; chlorosilane, as a silicon source, can react with other components to form silicon oxygen bonds, and improve the adhesion, heat resistance and chemical corrosion resistance of the coating. The high proportion of polytetrafluoroethylene ensures the high temperature resistance of the coating, while the addition of chlorosilane enhances the chemical corrosion resistance of the coating, especially the stability under high temperature environment. Nylon powder improves the wear resistance and mechanical strength of the coating, making the coating more durable in high friction environments. Nano zinc oxide improves the anti-ultraviolet, antibacterial and anti-pollution capabilities of the coating. Chlorosilane not only enhances the adhesion between the coating and the paper base, but also forms a cross-linked structure, further improving the stability and overall performance of the coating.

[0047] Preferably, the viscosity of the fluorocarbon coating is between 150 and 300 cP. The viscosity of the coating directly affects its coating uniformity, leveling and adhesion. Moderate viscosity avoids the problem of being too thick or too thin. When the viscosity is too high, the coating is difficult to apply evenly, and a thick or uneven coating may appear; when the viscosity is too low, the coating may not adhere well or be too thin, and the expected high temperature resistance and anti-pollution effect cannot be achieved.

[0048] Furthermore, in step S201, the temperature of the heating and stirring treatment is between 50 and 80°C. The heating and stirring helps to evenly mix the components such as polytetrafluoroethylene, nano zinc oxide, nylon powder and chlorosilane, avoids stratification or aggregation of the components, and ensures the stability and uniformity of the coating.

[0049] Preferably, the thickness of the silicon quantum dot layer is between 1 and 5 μm; the thickness of the fluorocarbon coating is between 5 and 15 μm; and the thickness of the paper-based raw material is between 50 and 150 μm.

[0050] Embodiment 1:

[0051] This embodiment provides a high temperature resistant release paper and a preparation method thereof, the steps are as follows:

[0052] S100, soaking the paper-based raw material in a 5 mg / mL silicon quantum dot solution, taking out the treated paper-based raw material, and freeze-drying it at a temperature of -50°C for 18 hours to obtain a modified paper-based raw material;

[0053] S210, placing the modified paper base into a plasma treatment device, and selecting oxygen for plasma treatment for 3 minutes;

[0054] S200, applying a fluorocarbon coating on the surface of the modified paper base to obtain a high temperature resistant release paper;

[0055] The preparation method of the silicon quantum dot solution adopts the following steps:

[0056] S110, dissolving lithium aluminum hydride in deionized water, and adding silicon tetrachloride to obtain a first mixed solution, wherein the mass ratio of silicon tetrachloride to lithium aluminum hydride is 1:1;

[0057] S120, transferring the mixed solution into a reaction kettle, heating the reaction at a temperature of 180° C. for 10 h, and cooling the mixture to obtain a second mixed solution;

[0058] S130, adding polyethylene glycol to the second mixed solution at a mass ratio of 1:100, and sequentially performing stirring treatment, centrifugation treatment, and washing treatment to obtain a silicon quantum dot solvent;

[0059] The preparation method of fluorocarbon coating adopts the following steps:

[0060] S201, adding polytetrafluoroethylene to a fluorinated solvent, and adding nano zinc oxide and nylon powder in sequence while heating and stirring at 65° C. to obtain a mixed solution;

[0061] S202, adding chlorosilane to the mixed solution to obtain a fluorocarbon coating;

[0062] Among them, the mass ratio of polytetrafluoroethylene, nano zinc oxide, nylon powder and chlorosilane is 6.8:3.6:2.8:1, and the viscosity of the fluorocarbon coating is 260cP.

[0063] Embodiment 2:

[0064] This embodiment provides a high temperature resistant release paper and a preparation method thereof, the steps are as follows:

[0065] S100, soaking the paper-based raw material in a 1 mg / mL silicon quantum dot solution, taking out the treated paper-based raw material, and freeze-drying it at a temperature of -40°C for 24 hours to obtain a modified paper-based raw material;

[0066] S210, placing the modified paper base into a plasma treatment device, and selecting oxygen for plasma treatment for 5 minutes;

[0067] S200, applying a fluorocarbon coating on the surface of the modified paper base to obtain a high temperature resistant release paper;

[0068] The preparation method of the silicon quantum dot solution adopts the following steps:

[0069] S110, dissolving hydrogen in deionized water, and adding trichlorosilane to obtain a first mixed solution, wherein the mass ratio of silicon tetrachloride to lithium aluminum hydride is 1:0.5;

[0070] S120, transferring the mixed solution into a reaction kettle, heating the reaction at a temperature of 140° C. for 24 hours, and cooling the mixture to obtain a second mixed solution;

[0071] S130, adding hexadecyltrimethylammonium chloride in a mass ratio of 1:10 to the second mixed solution, and performing stirring treatment, centrifugal treatment, and washing treatment in sequence to obtain a silicon quantum dot solvent;

[0072] The preparation method of fluorocarbon coating adopts the following steps:

[0073] S201, adding polytetrafluoroethylene to a fluorinated solvent, and adding nano zinc oxide and nylon powder in sequence while heating and stirring at 50° C. to obtain a mixed solution;

[0074] S202, adding chlorosilane to the mixed solution to obtain a fluorocarbon coating;

[0075] Among them, the mass ratio of polytetrafluoroethylene, nano zinc oxide, nylon powder and chlorosilane is 30:16:12:1, and the viscosity of the fluorocarbon coating is 150cP.

[0076] Embodiment 3:

[0077] This embodiment provides a high temperature resistant release paper and a preparation method thereof, the steps are as follows:

[0078] S100, soaking the paper-based raw material in a 10 mg / mL silicon quantum dot solution, taking out the treated paper-based raw material, and freeze-drying it at a temperature of -60°C for 12 hours to obtain a modified paper-based raw material;

[0079] S210, placing the modified paper base into a plasma treatment device, and selecting oxygen for plasma treatment for 1 minute;

[0080] S200, applying a fluorocarbon coating on the surface of the modified paper base to obtain a high temperature resistant release paper;

[0081] The preparation method of the silicon quantum dot solution adopts the following steps:

[0082] S110, dissolving sodium borohydride in deionized water, and adding silicon tetrachloride to obtain a first mixed solution, wherein the mass ratio of silicon tetrachloride to lithium aluminum hydride is 1:2;

[0083] S120, transferring the mixed solution into a reaction kettle, heating the reaction at a temperature of 220° C. for 2 h, and cooling the mixture to obtain a second mixed solution;

[0084] S130, adding polyacrylamide to the second mixed solution at a mass ratio of 1:200, and performing stirring treatment, centrifugal treatment, and washing treatment in sequence to obtain a silicon quantum dot solvent;

[0085] The preparation method of fluorocarbon coating adopts the following steps:

[0086] S201, adding polytetrafluoroethylene to a fluorinated solvent, and adding nano zinc oxide and nylon powder in sequence while heating and stirring at 80° C. to obtain a mixed solution;

[0087] S202, adding chlorosilane to the mixed solution to obtain a fluorocarbon coating;

[0088] Among them, the mass ratio of polytetrafluoroethylene, nano zinc oxide, nylon powder and chlorosilane is 4:2:1.6:1, and the viscosity of the fluorocarbon coating is 300 cP.

[0089] Comparative Example 1:

[0090] This comparative example provides a high temperature resistant release paper and a preparation method thereof, the steps are as follows:

[0091] S210, cleaning the paper base, placing it in a plasma treatment device, and selecting oxygen for plasma treatment for 1 minute;

[0092] S200, applying a fluorocarbon coating on the surface of the modified paper base to obtain a high temperature resistant release paper;

[0093] The preparation method of the fluorocarbon coating comprises the following steps:

[0094] S201, adding polytetrafluoroethylene to a fluorinated solvent, and adding nano zinc oxide and nylon powder in sequence while heating and stirring at 80° C. to obtain a mixed solution;

[0095] S202, adding chlorosilane to the mixed solution to obtain a fluorocarbon coating;

[0096] Among them, the mass ratio of polytetrafluoroethylene, nano zinc oxide, nylon powder and chlorosilane is 6.8:3.6:2.8:1, and the viscosity of the fluorocarbon coating is 260cP.

[0097] Comparative Example 2:

[0098] This comparative example provides a high temperature resistant release paper and a preparation method thereof, the steps are as follows:

[0099] S210, cleaning the paper base, placing it in a plasma treatment device, and selecting oxygen for plasma treatment for 1 minute;

[0100] S200, applying a fluorocarbon coating on the surface of the modified paper base to obtain a high temperature resistant release paper;

[0101] Among them, fluorocarbon coating was purchased from outside.

[0102] Performance Test:

[0103] (1) High temperature resistance test: The release paper samples of Examples 1-3 and Comparative Examples 1-2 were cut into uniform 50 mm × 50 mm pieces and placed in a high temperature oven with set temperatures of 100°C, 200°C, and 300°C and times of 1 h, 3 h, and 6 h. After heating, the samples were taken out, observed, and recorded. The results are shown in Table 1.

[0104] (2) Adhesion test: The release paper samples of Examples 1-3 and Comparative Examples 1-2 were cut into uniform 50 mm × 50 mm pieces, and a peel test was performed using a tensile testing machine at 150° C. The results are shown in Table 2;

[0105] (3) Thickness test: The thickness of each layer of the release paper samples of Examples 1-3 and Comparative Examples 1-2 was measured. The results are shown in Table 2.

[0106] Table 1

[0107]

[0108]

[0109] It can be seen from the above table that at 100°C and 200°C, the samples of Examples 1-3 performed well, with no obvious changes or only slight deformation, indicating that the material has better stability at lower temperatures. As the temperature increases to 300°C, the samples begin to show slight deformation and discoloration, compared with Comparative Examples 1-2, indicating that the combined treatment of silicon quantum dot solution and fluorocarbon coating in the present application significantly improves the high temperature resistance.

[0110] Table 2

[0111]

[0112] The adhesion of Examples 1-3 is relatively small, indicating that they have lower adhesion at 150°C, better release performance, and can effectively prevent adhesion; the adhesion of the control group is higher, indicating that the release performance is poor, and they may be more prone to adhesion compared to the examples.

[0113] Finally, it should be noted that the embodiments of the present disclosure have been described above, and the above description is exemplary, not exhaustive, and is not limited to the disclosed embodiments. Many modifications and changes are obvious to those of ordinary skill in the art without departing from the scope and spirit of the described embodiments. The choice of terms used herein is intended to best explain the principles of the embodiments, practical applications, or technical improvements in the market, or to enable other persons of ordinary skill in the art to understand the embodiments disclosed herein.

Claims

1. A method for preparing high temperature resistant release paper, characterized in that: The preparation method comprises the following steps: S100, soaking a paper-based raw material in a silicon quantum dot solution, taking out the treated paper-based raw material and performing freeze-drying treatment to obtain a modified paper-based raw material; S200, applying a fluorocarbon coating on the surface of the modified paper base to obtain the high temperature resistant release paper; The method for preparing the silicon quantum dot solution comprises the following steps: S110, dissolving a reducing agent in deionized water, and adding a silicon source to obtain a first mixed solution; S120, transferring the mixed solution into a reaction kettle, heating the reaction at a temperature of 140 to 220° C. for 2 to 24 hours, and cooling the mixture to obtain a second mixed solution; S130, adding a surface modifier to the second mixed solution, and performing stirring treatment, centrifugal treatment, and washing treatment in sequence to obtain a silicon quantum dot solvent.

2. The preparation method according to claim 1, characterized in that: In step S110, The silicon source comprises at least one of silicon tetrachloride and trichlorosilane; and / or The reducing agent comprises at least one of lithium aluminum hydride, hydrogen, and sodium borohydride; and / or The mass ratio of the silicon source to the reducing agent is 1:(0.5-2).

3. The preparation method according to claim 1, characterized in that: In step S130, The surface modifier comprises at least one of organosilane, polyethylene glycol, hexadecyltrimethylammonium chloride, sodium dodecylbenzenesulfonate, and polyacrylamide; and / or The mass ratio of the surface modifier to the second mixed solution is 1:(10-200).

4. The preparation method according to claim 1, characterized in that: In step S100, The solubility of the silicon quantum dot solution is between 1 and 10 mg / mL; and / or The freeze drying temperature is between -40 and -60°C; and / or The freeze-drying treatment time is between 12 and 24 hours.

5. The preparation method according to claim 1, characterized in that: Also included between step S100 and step S200: S210, performing plasma treatment on the modified paper base.

6. The preparation method according to claim 1, characterized in that: In step S200, the method for preparing the fluorocarbon coating comprises the following steps: S201, adding polytetrafluoroethylene to a fluorinated solvent, and adding nano zinc oxide and nylon powder in sequence while heating and stirring to obtain a mixed solution; S202, adding chlorosilane to the mixed solution to obtain the fluorocarbon coating.

7. The preparation method according to claim 6, characterized in that: In the fluorocarbon coating, the mass ratio of the polytetrafluoroethylene, the nano zinc oxide, the nylon powder and the chlorosilane is (30-4): (16-2): (12-1.6): 1; and / or The viscosity of the fluorocarbon coating is between 150 and 300 cP.

8. The preparation method according to claim 6, characterized in that: In step S201, The temperature of the heating and stirring treatment is between 50 and 80°C.

9. The preparation method according to claim 1, characterized in that: The thickness of the silicon quantum dot layer is between 1 and 5 μm; The thickness of the fluorocarbon coating is between 5 and 15 μm; The thickness of the paper-based material is between 50 and 150 μm.

10. A high temperature resistant release paper, characterized in that: The high temperature resistant release paper is prepared by the preparation method according to any one of claims 1 to 9.